Systemic side effects of ocular medication: Topical therapeutic drugs – part 2. Issue 8 (August 2020) - Gherghel, Doina
Abstract : Dr Doina Gherghel continues here review of adverse effects of ophthalmic drugs with a focus upon those used to treat ocular disease (C 76218, one distance learning CET point suitable for optometrists and therapeutic optometrists)